Adapted sport effect on postural control after spinal cord injury - Magnani, P. E.; Marques, N. R. [UNESP]; Junior, A. C.; Abreu, D. C. C. de (Nature Publishing Group, 2016)
Study design: Cross-sectional study. Objective: The aim of this study was to compare trunk muscle activation during anterior and lateral reach in athletic and sedentary individuals with spinal cord injury (SCI) and able-bodied people. Settings: University Hospital-UNICAMP, Campinas, Brazil. Methods: Individuals with complete traumatic SCI and thoracic neurological level were separated into two groups: sedentary (SSCI: n=10) and physically active (PASCI: n=10). The control group (C: n=10) without SCI was assessed. Trunk muscle activation was recorded during reach and grasp tasks. The significant level was set at P<0.05. Results: The control group showed a highest mean activation for left longissimus muscle during all activities (P<0.05). The PASCI group presented significant highest activation for left iliocostalis muscles during all activities, except in the anterior reach task of 90% maximum reach (anterior reach (AR) 75: P=0.02; right lateral reach (RLR) 75: P=0.03; RLR90: P=0.01). The SSCI group presented highest activation for the left iliocostalis during the right lateral reach task of 75 and 90% maximum reach and right iliocostalis during the anterior reach task of 75% maximum reach (AR75: P=0.007; RLR75: P=0.02; RLR90: P=0.03). A different pattern of muscle activation between the control group and the groups with SCI was observed. Conclusion: Our results indicated that sports practice did not affect the trunk muscle activation in people with paraplegia. However, the pattern muscle activation in individuals with SCI is different compared with people without SCI during anterior reach tasks.